2019
DOI: 10.1016/j.proci.2018.07.074
|View full text |Cite
|
Sign up to set email alerts
|

A shock tube and modeling study on the autoignition properties of ammonia at intermediate temperatures

Abstract: Ammonia (NH 3), has been considered as a promising alternative energy carrier for automobile engines and gas turbines due to its production from renewable sources using concepts such as power-togas. Knowledge of the combustion characteristics of NH 3 /air and the formation of pollutants, especially NO x and unburned NH 3 , at intermediate temperatures is crucially important to investigate. Detailed understanding of ammonia reaction mechanism is still lacking. The present study reports ignition delay times of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…Due to the low reactivity of ammonia and longer IDTs, the presence of non-ideal, dynamic effects must be taken into account in the simulation of experimental data at both intermediate-and low-temperature conditions. Therefore, for the intermediate-temperature shock tube (ST) measurements, 32 the experimental pressure profile of the single experiments was converted into volume profile, starting from the arrival time of the reflected shock wave until the time point equal to 90% of the measured IDT, after which the volume was kept constant. Constrained-volume 0D simulations were then performed using the obtained profile.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low reactivity of ammonia and longer IDTs, the presence of non-ideal, dynamic effects must be taken into account in the simulation of experimental data at both intermediate-and low-temperature conditions. Therefore, for the intermediate-temperature shock tube (ST) measurements, 32 the experimental pressure profile of the single experiments was converted into volume profile, starting from the arrival time of the reflected shock wave until the time point equal to 90% of the measured IDT, after which the volume was kept constant. Constrained-volume 0D simulations were then performed using the obtained profile.…”
Section: View Article Onlinementioning
confidence: 99%
“…On the other hand, several experimental campaigns carried out in the latest years in less conventional conditions (lower temperatures, high dilution levels and wider pressure ranges) have shown that the fundamental knowledge of ammonia kinetics is still far from complete: the available mechanisms have shown important deviations in the autoignition behavior in diluted conditions, both in hightemperature shock tubes (ST) 27 and low-to intermediatetemperature shock tubes 32 and rapid compression machines (RCM). 33,34 Similarly, flow reactor experiments of pure NH 3 oxidation under atmospheric 35 and high pressure 36 showed that the kinetic models were not always able to reproduce the experimental trends.…”
Section: Introductionmentioning
confidence: 99%
“…Since the flux analysis for pure ammonia using the same mechanism as applied here has been reported in Chapter 3 (albeit at somewhat higher temperature), this analysis focuses on the differences in reaction path caused by methane addition. As observed previously in Chapter 3 [70] and [23,24], the initial step in ammonia oxidation is to form NH2, with further oxidation proceeding via either H2NO or N2H4, following reaction of NH2 with HO2 or NH2. At 50% CH4, while the major oxidation path of NH3 is unaltered (except that the N2H4 channel is suppressed, with a flux lower than 5%), the analysis shows the participation of carbon-containing species as reactants with the nitrogen species.…”
Section: Kinetic Analysismentioning
confidence: 56%
“…Regarding the literature on ammonia ignition, a number of studies have assessed the ignition delay times of NH3 in shock tubes [22,23] and RCMs [13,24]. Mathieu and Petersen [22] reported shock tube measurements of ignition delay times of highly diluted NH3/O2 mixtures over a wide range of conditions, temperature (T = 1560-2455 K), pressure (P) in the range 1.4 -30 atm and equivalence ratio ( ) between 0.5 and 2.0, and presented a mechanism that predicted their measurements well.…”
Section: Chapter -3 -mentioning
confidence: 99%
See 1 more Smart Citation